2015
DOI: 10.1186/s40557-015-0067-y
|View full text |Cite
|
Sign up to set email alerts
|

Minnesota multiphasic personality inventory as related factor for post traumatic stress disorder symptoms according to job stress level in experienced firefighters: 5–year study

Abstract: ObjectivesAs first responders to an increasing number of natural and manmade disasters, active-duty firefighters are at increased risk for physical and psychiatric impairment as reflected by high rates of posttraumatic stress disorder (PTSD). Because little is known about related factor with PTSD according to job stress level among firefighters, we assessed utility of the Minnesota Multiphasic Personality Inventory (MMPI) using 5-year medical surveillance.MethodsData were analyzed from 185 male firefighters wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 29 publications
(30 reference statements)
1
29
0
Order By: Relevance
“…One of the major findings of trauma from previous research is that the majority of people are able to deal with their traumatic experiences well and rarely develop PTSD after a traumatic experience [2]. These findings suggest that for some workers, PTSD is an outcome of failure in recovery rather than the natural results of the traumatic exposure [37,38]. Studies have suggested that many factors determine the magnitude and duration of trauma responses.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major findings of trauma from previous research is that the majority of people are able to deal with their traumatic experiences well and rarely develop PTSD after a traumatic experience [2]. These findings suggest that for some workers, PTSD is an outcome of failure in recovery rather than the natural results of the traumatic exposure [37,38]. Studies have suggested that many factors determine the magnitude and duration of trauma responses.…”
Section: Discussionmentioning
confidence: 99%
“…It is also well documented that employee stress may negatively affect business performance since it has been associated with reduced productivity in the workplace [19]. Firefighters are exposed to many different workplace hazards that could lead to acute and/or chronic work-related stress throughout their career [20]. Particularly, firefighters' duties such as assisting, hoisting and carrying victims from accidents and/or fire scenes may be associated with extreme mental stress, especially when they involve fatalities of children and young adults [21].…”
Section: Data Collectionmentioning
confidence: 99%
“…The Impact of Event Scale-Revised (IES-R) scale is the most commonly used measure for screening emergency service workers for mental health problems [38][39][40][41][42]. The IES-R has a three-factor structure (eight items assessing intrusion, eight items assessing avoidance, and six items assessing hyperarousal).…”
Section: Predictor Variablesmentioning
confidence: 99%